Effect of Microwave-Assisted, Ultrasonic-Assisted, and Conventional Water Extraction on Bioactive Compounds and Antioxidant Activity of Black Ginger (Kaempferia parviflora) - phovisay, somsay; PHOMLASABOUD, Khantavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Black ginger (Kaempferia parviflora) is a valuable medicinal plant containing bioactive compounds. This study investigated the effects of different extraction methods on the yield of bioactive compounds and antioxidant activity from black ginger rhizomes. The dried samples were extracted using 3 different methods with water as solvent (1:20 w/v) for 5 minutes: microwave-assisted extraction (MAE), conventional boiling extraction, and ultrasonic-assisted extraction (UAE). Total phenolic content, total tannin content, total flavonoid content, antioxidant activity (DPPH inhibition), color parameters (L*a*b*), and optical density (OD600) were analyzed for each extraction method. The results indicated statistically significant differences among the extraction techniques (p<0.05). MAE demonstrated superior performance with the highest total phenolic content (19.68 mg GAE/g), total tannin content (11.42 mg TAE/g), total flavonoid content (6.66 mg QE/g), antioxidant activity (31.51% DPPH inhibition), and optical density (1.10), indicating the highest concentration of extracted compounds. MAE showed darkest color (L*=2.30, a*=12.33, b*=1.27). Conventional boiling extraction showed moderate efficiency with total phenolic content of 17.01 mg GAE/g, total tannin content of 9.65 mg TAE/g, total flavonoid content of 4.25 mg QE/g, 26.08% DPPH inhibition, intermediate optical density (0.70), and color values of L*=4.87, a*=25.33, b*=5.77. UAE exhibited the lowest extraction efficiency across all parameters, yielding total phenolic content of 10.95 mg GAE/g, total tannin content of 6.34 mg TAE/g, total flavonoid content of 2.30 mg QE/g, 21.27% DPPH inhibition, lowest optical density (0.34), and lightest color (L*=25.67, a*=24.67, b*=7.97). The findings indicate that MAE is the most effective method for maximizing bioactive compound recovery and antioxidant activity from black ginger, offering potential applications in functional food and supplement industries.